Determination of Diabetes type 2 Clients’ Self-Management Skills toward Dietary Pattern - Oleiwi, Sameer; AL Ani, Batool (Iraqi National Journal of Nursing Specialties, 2012)
Objective: study aims to identify the diabetes type2 clients self management skills toward dietary pattern , and find out the relationship between variables which are (Age, gender, educational level, duration of DM diagnosis, and monthly income) with diabetes type 2 clients self management skills toward dietary pattern Methodology: descriptive study was carried out through the present investigation from January 2nd 2011to September 2nd 2011 in order to achieve the objectives of the present study. A non probability (purposive) sample, (200) cases which consists of clients who were attending Al-Nasiriyha diabetic center. Including (118) males and (82) females. The data were collected by utilization of the study instruments and employment of scheduled interview as means data collection. The data collection process was performed from April /30/ 2011 to Jun / 3rd/ 2011. A questionnaire was designed constructed by the researcher to measure the variable. Such a construction was employed through the review of literature and related studies. The questionnaire consisted of 2 parts which are demographical, and diabetics self management skills indicator dietary pattern .The reliability of the questionnaire was determined through a pilot study and the validity through a panel of experts. The data were analyzed through the application of descriptive statistic frequency, percentage, and the application of inferential statistical procedures, which include Pearson correlation coefficient, and contingency coefficient. Results: Highest percent of the study samples (37.5) were (50-59) years old. With the mean age (52) years, (72.0) of them are without of diabetes type 2 self management skills toward dietary pattern, most of them were male. With low educational level. Group’s duration of type 2 DM diagnosis was (1-5) years. Insufficient monthly income, unemployed, overweight. They had information from their physician, and diagnosed by chance. There are significant association between diabetes type 2 clients’ self management skills toward 40 dietary pattern and (age, educational level, monthly income).And there were no significant association with another variable. Recommendations: The researcher recommended that the new diabetic patients should be involve in educational program , supply with booklet which include self management skills toward dietary pattern and supported by videotapes to enforce their practices , with the nurse supervision during visit them to the center , and instructed to improve their life management skills for control their blood glucose and body weight to avoid long term complications.